A Strategy for Screening and Confirmation of HTLV-1/2 Infections in Low-Endemic Areas - Ji, Huimin; Chang, Le; Yan, Ying; Jiang, Xinyi; Sun, Huizhen; Guo, Fei; Wang, Lunan (Frontiers in Microbiology, 2020)
Serological tests have been widely used for detecting human T-cell lymphotropic virus type 1/2 (HTLV-1/2) antibodies in the endemic areas, but their performance in low-risk populations is rarely reported. The aim of this study was to evaluate the performance of four HTLV-1/2 screening assays and to discuss a strategy for diagnosis of HTLV-1/2 infection in a non-endemic area. At the present study, 1546 specimens repeatedly reactive (RR) by one screening ELISA were collected from blood centers/banks from January 2016 to April 2019. Avioq-ELISA, Murex-ELISA, Roche-ECLIA and Fujirebio-CLIA were independently performed on each plasma sample and compared to WB and LIA confirmatory tests. Positive or indeterminate specimens with blood available were quantified by qPCR. The results showed that 48 samples were finally confirmed as HTLV-1 positive, 13 were HTLV positive, 151 were indeterminate and 387 were negative. All the WB-positive samples were also LIA-positive. Roche-ECLIA showed the highest sensitivity that was able to detect 91.8% positives and combined with the Murex-ELISA would significantly increase the positive detection rate (98.4%). In addition, LIA yield more indeterminate and HTLV-untyped results than WB (152 vs. 27), but was able to resolve infection status of some individuals with an indeterminate WB. Besides, 3 WB indeterminate and 1 LIA-untyped samples were confirmed as HTLV-1 positive by qPCR. Based on these findings, we put forward a proper test strategy for HTLV-1/2 diagnosis in low-prevalence areas. If possible, the Roche-ECLIA with the highest sensitivity is suggested as a second screening assay in primary labs. If not, all RR specimens are recommended to be firstly retested by Roche-ECLIA and Murex-ELISA in the reference lab. Secondly, samples reactive to any one of the two tests were quantified by qPCR, and then the NAT-negatives were furtherly submitted to LIA for confirmation. Thereby, the cost can be reduced and the diagnostic accuracy would be improved.